Tectonics of Enceladus’ South Pole: Block rotation of the Tiger Stripes - Rossi, Costanza; Cianfarra, Paola; Salvini, Francesco; Bourgeois, Olivier; Tobie, G. (Journal of Geophysical Research: Planets, 2020)
International audience • Tectonic activity at Enceladus' south pole is consistent with clockwise block rotation tectonics. • Regional right-lateral strike-slip kinematics induces transtensional and transpressional regimes in the south polar region. • An evolutionary tectonic model is proposed for the past, present and future settings of Enceladus' south polar structures.